The medical philosopher (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
By means of a historical review of the links established between philosophy and medicine, this article examines these relations considering four aspects; a) the problem of the understanding of life elaborated by medicine and the determinism present in its scientific actions of knowledge; b) the variable of indeterminacy that human subjectivity introduces before these efforts of objectification; c) the notion of normativity elaborated by G. Canguilhem, its presence in human life and in the manifestations of disease; d) the philosophical analysis of the system of norms existing in the elaborations of Canguilhem and its incidence in the statements of human life and in the manifestations of disease. Canguilhem, its presence in human life and in the manifestations of disease; d) the philosophical analysis of the system of norms existing in Canguilhem’s elaborations and its incidence in Michel Foucault's biopolitical statements.
Keywords: Life; Norm; Biopolitics; Normal; Disease